Optimizing Geothermal Energy Extraction in CO2 Plume Geothermal Systems - Sofianos Panagiotis Fotias; Spyridon Bellas; Vassilis Gaganis (Materials Proceedings, 2023)
CPG (CO2 Plume Geothermal) has recently emerged as a promising technology to combine the extraction of geothermal energy with underground CO2 storage, thus achieving double positive results. The idea is to inject CO2 in its supercritical form to create a plume and replace the reservoir brine, which is continuously circulated to transfer heat from the reservoir to surface facilities. Apart from the positive aspects of this technology, including the reduced energy to inject and lift the working fluid as well as its enhanced mobility in the reservoir and reduced environmental footprint, there are also negative issues that must be handled by adequately studying the geological field/reservoir and appropriately designing the production system. In this work, we present a finite volume numerical simulation that can study a geothermal reservoir from its geological origin to the dynamic simulation of CO2 injection and estimate the geothermal energy extraction. It is shown that the system performance is strongly related to the selected schedule, and optimizing it in conjunction with the related cost is of the utmost importance for the Final Investment Decision to be taken and for the viability of such multipurpose projects under a sustainable future.